Heading in female soccer: a scoping systematic review - Shen, Y.; Chen, S.; Liu, Q.; Cicchella, A. (Sports, 2024)
Heading is a key skill in soccer, and it is few investigated in females. Research on heading focused mostly on males and on young players. Data on females` soccer players are sparse and it is difficult to draw firm conclusions. Thus, little is known is known about heading in females. The most investigated aspects of heading are the relationship between heading and play state, training level and anthropometrics. The relationship between the frequency and intensity of headings and long-time outcomes in terms of vigilance, and neuro-cognitive status is also a topic of interest. Aim of this scoping review is to survey the available knowledge about heading in female football to identify possible weaknesses and issues for future research direction in the field. A structured literature search was performed in the main databases. Results show research on heading in female soccer is sparse and to draw firm conclusion on the investigated aspects (effect of play position, occurrence, cognitive impairment, influence of muscle strength, and player`s level) is difficult. It emerged mild intensity heading is not dangerous, helmet does not help, play state and player position influences the heading and that high rotational velocities are achieved. The survey identified new directions for research, that should focus on how to ameliorate heading training and skills and develop a more effective and safe heading technique.